Comparison of the effect of Sodium hypochlorite and Chlorhexidine gluconate as denture cleansers on some properties of heat-cured acrylic“An in vitro study" - سلمان, مجد; أحمد, محمد عدنان (Latakia University Journal -Medical Sciences Series, 2021)
Disinfection of acrylic prosthetic devices aims to maintain a healthy oral environment, which prevents fungal and other pathogens, as oral health is linked to the cleanliness of prosthetic devices. This study aims to compare the effect of both 0.5% sodium hypochlorite solution and (0.12%) chlorhexidine gluconate solution on the weight change of samples of heat cured acrylic resin by the traditional method (water absorption or loss) compared with distilled water, for six-month period of using disinfectants that prosthetic devices immersed in. The study sample included 30 samples of heat cured acryl, rectangular samples (2-4) cm, 3 mm thickness. The results of the statistical analysis showed that the difference in the soaking solution, whether it was (0.12%) chlorhexidine gluconate solution or (0.5%) sodium hypochlorite solution, did not differ in its effect on the weight of the heat-cured acrylic resin compared with the distilled water (control liquid). Within the limits of this study, we conclude that there is no difference in the use of one of the disinfection solutions, chlorhexidine gluconate (0.12%) or a solution of sodium hypochlorite (0.5%), on the weight of heat cured acrylic resin from which the bases of the removable dentures are made.